Are incidentally detected gall bladder cancers really incidental? A report of two cases from a developing nation. (October 2018) - Gupta, Ashish; Gupta, Amit; Gupta, Sweety; Chauhan, Udit; Joshua, Lokavarapu Manoj
Gallbladder cancer (GBC) is a rare gastrointestinal tumour. It occurs in women with pre-existing cholelithiasis. These tumours pose therapeutic as well as diagnostic challenges to treating clinicians. Early suspicion and optimal surgery for suspected GBC results in the best outcome. We describe two cases of metastatic GBC initially treated by simple cholecystectomy for gallstone despite disease pointers towards a malignant pathology. Subsequent presentation was with histopathologically proven metastatic GBC. In an area of high gallsone prevalence, a high index of suspicion and correct management of patients with suspicion of GBC is mandatory.